2008
DOI: 10.1158/1055-9965.epi-07-0771
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Survival after Diagnosis of Invasive Breast Cancer

Abstract: Previous studies suggest that increased physical activity may lower the risk of breast cancer incidence, but less is known about whether levels of physical activity after breast cancer diagnosis can influence survival. We prospectively examined the relation between postdiagnosis recreational physical activity and risk of breast cancer death in women who had a previous invasive breast cancer diagnosed between 1988 and 2001 (at ages 20-79 years). All women completed a questionnaire on recent postdiagnosis physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
298
2
15

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(340 citation statements)
references
References 34 publications
(30 reference statements)
25
298
2
15
Order By: Relevance
“…Many participants began exercising in an effort to improve their health. This result is similar to othersstudies that have indicated that exercise can enhance health and prevent cancer recurrence (Norman et al, 2007;Holick et al, 2008;Weiner et al, 2010;Magné et al, 2011). The results of this study show that many participants practiced Qigong to restore balance to the body.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Many participants began exercising in an effort to improve their health. This result is similar to othersstudies that have indicated that exercise can enhance health and prevent cancer recurrence (Norman et al, 2007;Holick et al, 2008;Weiner et al, 2010;Magné et al, 2011). The results of this study show that many participants practiced Qigong to restore balance to the body.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, other studies have pointed toward cancer survivors attempted to change their unhealthy behaviors (Norman et al, 2007;Demark-Wahnefried et al, 2008 ;Holick et al, 2008;Weiner et al, 2010;Magné et al, 2011). Chinese culture emphasizes health preservation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar results were found by a cohort study of 4,482 invasive breast cancer patients [13] and for two studies that investigated the relationship between breast cancer mortality and pre-diagnostic physical activity [14,15]. Results from the WHEL study indicated that the combination of consuming at least five servings of vegetables-fruits and physical activity (30 min of walking at moderate pace for 6 days a week) is associated with an increase in survival in women with estrogen-positive receptor tumours [16].…”
Section: Physical Activitysupporting
confidence: 91%
“…Systematic reviews conclude that exercise is a safe and feasible supportive intervention associated with significant improvements in patient-reported outcomes (e.g., quality of life, fatigue) as well as physiological outcomes (exercise tolerance, muscle strength) in cancer populations (3,21). Moreover, several landmark epidemiologic studies have provided the first evidence that regular moderate-intensity exercise is associated with a 30 -50% reduction in the risk of cancer-specific mortality and all-cause mortality following a diagnosis of early breast or colorectal cancer (14,16,28). As such, elucidation of the molecular mechanisms underlying this association is of paramount importance to optimize the safety and efficacy of exercise in cancer control.…”
mentioning
confidence: 99%